The importance of documenting the casualties of armed conflict - Emily Ward; Lily Hamourtziadou (Journal of Global Faultlines)
This article highlights the importance of documenting casualties of armed conflicts. It looks at the Oxford Research Group’s list of legal obligations of states to document casualties. This list has been compiled from multiple different laws that are currently in place for conflicts but are often ignored or forgotten due to other pressing matters. It will also look at how mass deaths have been recorded strategically by states, by comparing the record keeping from the COVID-19 pandemic to record keeping in armed conflicts. It examines the work of NGOs, such as Iraq Body Count, and addresses the issue of accountability. Finally, it uses the Bouderbala Commission as a positive example of a government working together with its citizens to help create documentation of a conflict.